Pengaruh Pendidikan Kesehatan Jiwa Keluarga Terhadap Pengetahuan Dan Sikap Pencegahan Kekambuhan Gangguan Jiwa Di Desa Makamhaji Kecamatan Kartasura Kabupaten Sukoharjo - Kusumaningtyas, Reny; , Arif Widodo, A.Kep, M.Kes; , Kartinah, S.Kep (2017)
Mental disorders are psychological or behavioral disorders that occur in person, generally associated with affective disorders, behavioral, cognitive and perceptual. Data showed the tendency decrease of people with mental disorders in the world and in Indonesia. One of the critical points in the treatment of mental patients is when the mental patients have undergone treatment and stayed with the family at home. At this time the role of families in preventing recurrence of mental disorders is very large. This study aims to determine the effect of family mental health education on knowledge and attitude of recurrence prevention of mental disorders in the village Makamhaji Kartasura District of Sukoharjo district. This study is a pre experimental with one group pre test and post test design. Samples were 30 relatives of patients with mental disorders in the village Makamhaji Kartasura District of Sukoharjo district with proportional random sampling technique. Collecting data using questionnaires were analyzed using the Wilcoxon rank test test and paired sample t-test. Conclusion of the study are (1) there are significant differences pre test and post test knowledge and attitudes about the prevention of relapse of psychiatric disorder after getting health education to families of patients with mental disorders in the village of Makamhaji District of Kartosuro, where the knowledge and attitude family decrease and ( 2) there is influence of health education on knowledge and attitudes about the prevention of recurrence of mental disorders in the village of the District Makamhaji Kartosuro.